Kedalaman Klorofil Maksimum Selama Musim Peralihan II dan Implikasinya untuk Perikanan Tuna di Laut Banda - Waas, Harold J.D; Tubalawony, Simon; Hukubun, Ronald D (Jurnal Laut Pulau: Hasil Penelitian Kelautan, 2023)
The Deep chlorophyll maximum (DCM) in the Banda Sea during the second transitional season (October 2015) was relatively shallow (25 - 64 m) above the mixed layer and far from the base of the euphotic layer or compensation depth. Its presence was identical to the depth of nitraclin injected into the mixed layer as a result of upwelling generated by internal waves. The contribution of these waves to the increase in Banda Sea fertility calculated using ocean color data is 56.87%. This phenomenon is due to the shallow optical depth of the satellite (20-25 m) while high chlorophyll-a concentrations are below. DCM was also associated with the swimming layer of Madidihang (Thunnus albacares) (34 - 68 m) caught with longline gear during the same period.